Adaptive phenotypic divergence in an annual grass differs across biotic contexts. (26th August 2019) - O'Brien, Anna M.; Sawers, Ruairidh J.H.; Strauss, Sharon Y.; Ross‐Ibarra, Jeffrey
Abstract: Climate is a powerful force shaping adaptation within species, yet adaptation to climate occurs against a biotic background: species interactions can filter fitness consequences of genetic variation by altering phenotypic expression of genotypes. We investigated this process using populations of teosinte, a wild annual grass related to maize ( Zea mays ssp. mexicana ), sampling plants from 10 sites along an elevational gradient as well as rhizosphere biota from three of those sites. We grew half‐sibling teosinte families in each biota to test whether trait divergence among teosinte populations reflects adaptation or drift, and whether rhizosphere biota affect expression of diverged traits. We further assayed the influence of rhizosphere biota on contemporary additive genetic variation. We found that adaptation across environment shaped divergence of some traits, particularly flowering time and root biomass. We also observed that different rhizosphere biota shifted expressed values of these traits within teosinte populations and families and altered within‐population genetic variance and covariance. In sum, our results imply that changes in trait expression and covariance elicited by rhizosphere communities could have played a historical role in teosinte adaptation to environments and that they are likely to play a role in the response to future selection.